2009
DOI: 10.1055/s-0029-1211350
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the effects of steroid hormone deprivation elicited by ovariectomy or ovariectomy plus adrenalectomy on the affinity and density of GABA binding sites in distinct rat brain areas

Abstract: The time course of the behaviour of GABAA receptors (affinity of muscimol for GABA binding sites and their number) in membranes obtained from five distinct rat brain areas was evaluated in dependence of the decline of the serum concentrations of estradiol and progesterone following hormone deprivation by either ovariectomy (OVX) or ovary- plus adrenalectomy (OVX-ADX) after 1, 2, 3, 5, 14 and 30 days. Diestrus rats served as control. The effect of OVX on the GABA binding sites was due to a decrease of affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Consistent with this conclusion, long term-treatment of rats wiTHPesterone induces up-regulation of GABA and benzodiazepine binding sites in specific brain regions (Gavish et al, 1987;Canonaco et al, 1989). Furthermore, steroid hormone deprivation by ovariectomy or adrenalectomy (or both) results in a decrease in GABA A receptor density in rat brain (Jussofie et al, 1995). The increase in the brain concentrations of neuroactive steroids during the first 19 days of pregnancy can thus be considered comparable to the long-term administration of high doses of these compounds, whereas the marked decrease in the concentrations of progesterone and its metabolites apparent at the end of pregnancy and after delivery is similar to a sudden discontinuation of such treatment.…”
Section: Pregnancy: An In Vivo Model Of Long-term Exposure To Progestsupporting
confidence: 63%
“…Consistent with this conclusion, long term-treatment of rats wiTHPesterone induces up-regulation of GABA and benzodiazepine binding sites in specific brain regions (Gavish et al, 1987;Canonaco et al, 1989). Furthermore, steroid hormone deprivation by ovariectomy or adrenalectomy (or both) results in a decrease in GABA A receptor density in rat brain (Jussofie et al, 1995). The increase in the brain concentrations of neuroactive steroids during the first 19 days of pregnancy can thus be considered comparable to the long-term administration of high doses of these compounds, whereas the marked decrease in the concentrations of progesterone and its metabolites apparent at the end of pregnancy and after delivery is similar to a sudden discontinuation of such treatment.…”
Section: Pregnancy: An In Vivo Model Of Long-term Exposure To Progestsupporting
confidence: 63%
“…Nevertheless, we can not discard the possibility of other element of the molecular dynamic in the NTS mechanisms of the baroreflex i.e., neurotransmitter release, receptor function and timing of responses on the absence of alteration in the method based on immunolabeling employed here. In support of this, decreases in the number of GABA binding sites and inhibition of NPY gene expression were seen in the medulla oblongata only 3 and 12 days after adrenalectomy, respectively (Jussofie et al 1995;Savontaus et al 2002). The present analysis also demonstrated that CGRP, GAL and NT immunoreactivities in the NTS seem to be modulated by kainate injection only in the absence of adrenal hormones.…”
Section: Discussionsupporting
confidence: 83%